2000
DOI: 10.1097/00000539-200012000-00033
|View full text |Cite
|
Sign up to set email alerts
|

Interscalene Brachial Plexus Block with a Continuous Catheter Insertion System and a Disposable Infusion Pump

Abstract: Continuous interscalene brachial plexus blockade traditionally requires a hospital stay for local anesthetic infusion, and achieving consistent catheter insertion may be difficult. Incorporating long-acting pain relief from a continuous peripheral nerve block, with a reliable method of catheter insertion, and a self-contained infusion system would be a valuable asset for short-stay care. We compared the efficacy of single injection interscalene brachial plexus blockade to a continuous peripheral nerve block, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(96 citation statements)
references
References 12 publications
2
91
0
3
Order By: Relevance
“…Similarly, Klein et al 18,19 observed technical difficulties with continuous interscalene block in 9-44% of adult cases. Recently, Capdevila et al…”
Section: Adverse Eventsmentioning
confidence: 86%
“…Similarly, Klein et al 18,19 observed technical difficulties with continuous interscalene block in 9-44% of adult cases. Recently, Capdevila et al…”
Section: Adverse Eventsmentioning
confidence: 86%
“…In addition, initial interscalene blockade was successful in all patients and all catheters were functional after 24 h with the continuous catheter insertion system. The authors concluded that it is possible to achieve a high rate of successful catheter placement and analgesia by using the continuous catheter insertion system and a disposable infusion pump in the ambulatory setting [11] . Ilfeld BM et al conducted a study to determine if the basal rate of an Interscalene perineural ropivacaine infusion could be decreased by 50% with a concurrent 200% increase in patientcontrolled bolus dose without compromising infusion benefits in ambulatory patients undergoing moderately painful orthopedic shoulder surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations many randomized controlled trials have demonstrated that use of Interscalene brachial plexus block with continuous catheter insertion system and disposable infusion pump is associated with better analgesic effect, reduced requirement of opioid analgesics and overall feeling of improvement in patients undergoing shoulder surgeries [7] . Popularity of this technique is increasing with point of care ultrasound (POCUS) using high frequency probes (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). With the use of ultrasound imaging excellent gray scale images of brachial plexus and its trunks, cords and divisions can be well demonstrated which consequently greatly improve accuracy with which perineural catheter is placed.…”
Section: Introductionmentioning
confidence: 99%
“…Catheter patency or secondary catheter block has been identified in many studies as a major mode of failure of CPNB with rates ranging from 10%-20% [59][60][61] 63 , fluid leakage at the catheter site 59 and dislodgement or obstruction of the tubing 64 . Incorrect catheter placement 65 , despite the significant increase in placement accuracy with the use of ultrasound guidance, also still remains an issue.…”
Section: Continuous Peripheral Nerve Blockade (Cpnb)mentioning
confidence: 99%